Book Banning Discourse and American Society in Ray Bradbury’s Fahrenheit 451 - Izzaty Irsyad (English Department, Faculty of Humanities, Andalas University, 2015)
This article discusses Ray Bradbury’s Fahrenheit 451 using a Foucauldian perspective. The novel depicts a dystopian society living under discourse surveillance in which books are banned. There are two contradicting discourses in the novel. First, book banning discourse which is constructed as system surveillance, makes people live in uniformity and lose independent thoughts. Second, freedom of reading discourse posits that reading and books play a vital role in society. The writer finds that book banning discourse influences the society and eliminates freedom of speech. Thus, in order to free the society from the authority surveillance, the freedom of reading must be restored.Keywords: science fiction, book banning, discourse, surveillance, freedom